Cyclic Amplification of Prion Protein Misfolding - Barria, Marcelo A (2012)
Protein Misfolfing Cyclic amplification (PMCA) is a technique that take advantage of the nucleation-dependent prion replication process to accelerate the conversion of PrP(C) into PrP(Sc) in the test tube. PMCA uses ultrasound waves to fragment the PrP(Sc) polymers, increasing the amount of seeds present in the infected sample without affecting their ability to act as conversion nucleus. Over the past 5 years PMCA has became an invaluable technique to study diverse aspects of prions. The PMCA technology has been used by several groups to understand the molecular mechanism of prion replication, the cellular factors involved in prion propagation, the intriguing phenomena of prion strains and species barriers, to detect PrP(Sc) in tissues and biological fluids and to screen for inhibitors against prion replication. In this article we describe a detailed protocol of the PMCA technique, highlighting some of the important technical aspects to obtain a successful and reproducible application of the technology.